Relación entre personalidad y desempeño académico de adolescentes en instituciones educativas públicas y privadas - Zambrano Vacacela, Luís Leonardo (Revista scientific, 2020)
The objective of the study is to determine the relationship between personality factors and the academic performance of adolescents in public and private educational institutions. The research was based on a non-experimental quantitative approach with a causal transectional design, for this the Personality Questionnaire for Adolescents (HSPQ) was applied to 136 students from 13 to 16 years old belonging to the ninth grade of Basic General Education in tax and private establishments of the rural sector in the city of Cuenca-Ecuador. The results reveal that women tend towards submission, responsibility and group work, while men tend to irresponsibility, aggressiveness and non-compliance with norms. Additionally, there is a minimal correlation between personality and academic performance and, finally, students from private institutions. achieves better grades in the general average than the students of tax establishments.El objetivo del estudio es determinar la relación entre factores de personalidad y el desempeño académico de adolescentes en instituciones educativas públicas y privadas. La investigación se fundamentó en un enfoque cuantitativo no experimental con diseño transeccional causal, para esto se aplicó el Cuestionario de Personalidad para Adolescentes (HSPQ) a 136 discentes de 13 a 16 años pertenecientes a noveno grado de Educación General Básica en establecimientos fiscales y particulares del sector rural en la ciudad de Cuenca-Ecuador.  Los resultados revelan que las mujeres tienden hacia la sumisión, responsabilidad y trabajo grupal, mientras que los hombres a la irresponsabilidad, agresividad e incumplimiento de normas, adicionalmente, existe correlación mínima entre la personalidad y el desempeño académico y, finalmente el alumnado de instituciones privadas alcanza mejores calificaciones en el promedio general que el estudiantado de establecimientos fiscales